Azathioprine‐induced pancytopenia: A case report. Issue 3 (17th July 2022) - Sigdel, Keshav Raj; Thapa, Astha; Dahal, Agnimshwor; Panthi, Ramchandra; Adhikari, Krishan; Shrestha, Pradeep; Lama, Mipsang; Poudyal, Buddhi; Basnyat, Buddha
Abstract: Azathioprine (AZA) is commonly used as immunosuppressive therapy for autoimmune diseases, including systemic lupus erythematosus (SLE). Myelosuppression is a common side effect of AZA. Here we report a case of severe myelosuppression following AZA therapy in a 15‐year‐old girl despite a normal thiopurine methyltransferase (TPMT) level. She had been receiving AZA for SLE and presented with neutropenic fever and pancytopenia. AZA was stopped. After stopping AZA, her blood counts steadily improved. When TPMT genotyping results were normal, AZA was reintroduced. Pancytopenia reappeared after starting AZA, despite normal TPMT genotype. AZA was replaced with mycophenolate mofetil which consequently resulted in improvement of blood counts. It is essential to understand the temporal relationship between AZA use and pancytopenia onset in patients with normal TPMT activity. This case illustrates that regular monitoring of blood cell counts should be routine practice after starting AZA regardless of TPMT activity. Abstract : We report a case of severe myelosuppression following azathioprine (AZA) therapy in a 15‐year‐old female despite a normal thiopurine methyltransferase (TPMT) genotype. In patients with systemic lupus erythematosus (SLE), the distinction between disease‐related and drug‐induced myelosuppression is often difficult. Given the sequential relationship of AZA initiation with myelosuppression and its withdrawal with recovery, AZA‐induced myelosuppression seemed a reasonable explanation in our patient's case. This report highlights the importance of regular complete blood count monitoring in patients receiving AZA therapy despite their TPMT levels. Key points: Azathioprine‐induced myelosuppression can occur in patients with normal thiopurine methyltransferase (TPMT) activity. Total cell counts should be evaluated on a frequent basis after initiating azathioprine even in patients with normal TMPT activity.